Efficient, cell-type-specific production of flavonols by multiplexed CRISPR activation of a suite of metabolic enzymes - Anaxi Houbaert; Valérie Denervaud Tendon; Lukas Hoermayer; Nicholas Morffy; Lucia C. Strader; Niko Geldner (Nature Communications)
Abstract Synthetic biology in plants promises to transform basic and applied research by rewiring entire developmental modules, signaling cascades or metabolic pathways. Yet, this requires expression of many genes simultaneously, very difficult with classic transgenic approaches, especially for the generation of stable traits. CRISPR activation systems work in plants and could greatly facilitate multiplexed gene activation. Current CRISPR activation systems are efficient for transient or ubiquitous expression. Yet, to fulfill their potential, CRISPR activation needs to perform robustly in specific organs and tissue types. Here, we present a CRISPR activation system that efficiently drives expression in a cell-type-specific manner in stable lines, which requires assessing expression on a cellular basis using fluorescent reporter lines. Our CRISPR systems consistently re-wire gene expression at the cellular level, inducing genes with cell-type specific expression to efficiently express in a new cell layer, such as root endodermis or epidermis. We demonstrate the power of our system to drive functionally relevant, multiplexed gene activation by achieving endodermis-specific production of wild-type levels of flavonoids, detectable by in-situ fluorescence, in a root-flavonoid deficient myb12 mutant.